Deux décennies de formation des enseignants dans les IUFM : un processus de formation professionnalisante en héritage - Marguerite Altet (Nantes Université, 2010)
The article attempts to show that the last two decades of teachers' training in the IUFM (Institut Universitaire de Formation des Maîtres / Master training university institute) engaged a genuine process of professionalization of the training, breaking with previous modeling training. From the founding principles established by the Ministry of Education, has been developed a new paradigm of professional training that sets priority to a practical purpose (building, developing competences necessary for practice) and involves both appropriation of various professional knowledge, know-how and know-being, but also the development of a reflexive stance by reflecting on action and its theorization. With a new training curriculum focusing on alternation and including professional knowledge and a ability's referential, the aim is to build the professionalism of a professional reflexive and autonomous teacher through various integrating devices.This process has definitely been implemented to various degrees in the IUFM and produced different identities depending on the persons. But the recent decision of integrating IUFM in universities and the will of a Mastering, might jeopardize the progress of professionalization if the professionalizing training curriculum, progressively built and acquired from twenty years of experience, is not appropriate by universities and is being questioned.